Five new species and new records of biting midges of the genus Dasyhelea Kieffer from the Near East (Diptera: Ceratopogonidae) - Dominiak, Patrycja; Alwin, Alicja (Zootaxa, 2013)
As a result of the entomological surveys in the Near East, seventeen species of biting midges of the genus Dasyhelea Ki-effer are reported. Five new species are described and illustrated from adult males: D. (Dicryptoscena) antonii sp. nov., D. (Pseudoculicoides) avia sp. nov., D. (Ps.) libanensis sp. nov., D. (Ps.) nauta sp. nov. and D. (Ps.) sandrageorgei sp. nov. Among the remaining species, four are recorded for the first time from this region. Furthermore, new country records for Iran (1 sp.), Israel (2 spp.), Lebanon (9 spp.) and Yemen (1 sp.) are given. Four species described by Kieffer in 1918, namely D. distalis, D. flaviscapula, D. scutellaris and D. trifasciata, are treated as doubtful names (nomina dubia) and excluded from the Turkish fauna. In addition, an updated checklist of Dasyhelea of the Near East is presented. Dasyhelea labinoda Mazumdar & Chaudhuri, 2009 is proposed as a new junior synonym of D. deemingi Boorman & Harten, 2002. New synonymy.